rozwiąż nierówność a) 1-9x^2> 0 , b) 3x^2-7x>5x^2+9x​



Odpowiedź :

Odpowiedź

a)

    [tex]x \in \left ( \dfrac {\, -1 \,} 3, \dfrac {\, +1 \,} 3 \right )[/tex]

b)

    [tex]x \in \left ( 0, 8 \right )[/tex]

Szczegółowe wyjaśnienie

  a)  1 - 9x^2 > 0

       [tex]1 - 9x^2 > 0\\\\\dfrac 1 9 - x^2 > 0\\\\\\\left ( \dfrac 1 3 \right ) ^2 - x^2 > 0\\\\\\\left ( \dfrac 1 3 - x \right ) \cdot \left ( \dfrac 1 3 + x \right ) > 0[/tex]

      [tex]- \left ( \dfrac 1 3 - x \right ) \cdot \left ( \dfrac 1 3 + x \right ) < 0 \\\\\\\left ( - \dfrac 1 3 + x \right ) \cdot \left ( \dfrac 1 3 + x \right ) < 0 \\\\\\\left ( x - \dfrac 1 3 \right ) \cdot \left ( x + \dfrac 1 3 \right ) < 0[/tex]

b)   3x^2 - 7x > 5x^2 + 9x

      [tex]3x^2 - 7x > 5x^2 + 9x\\\\3x^2 - 7x - 5x^2 - 9x > 0\\\\- 2x^2 - 16x > 0\\\\-2 \cdot x \cdot (x - 8) > 0\\\\x \cdot (x - 8) < 0[/tex]​

     

Odpowiedź:

                a)   [tex]\bold{x\in\big(-\frac13\,,\ \frac13\big)}[/tex]

                b)   [tex]\bold{x\in\big({-}8,\,0\bold)}[/tex]

Szczegółowe wyjaśnienie:

a)

    [tex]1 - 9x^2 > 0\\\\ 1 - (3x)^2 > 0\\\\(1-3x)(1+3x)>0\\\\1-3x_1=0\qquad\qquad1+3x_2=0\\-3x_1=-1\qquad\qquad 3x_2=-1\\{}\quad x_1=\frac13\qquad\qquad\quad\ x_2=-\frac13\qquad\qquad\quad a=-9<0\\\\x\in\big(-\frac13\,,\ \frac13\big)[/tex]

b)  

    [tex]3x^2-7x>5x^2+9x\\\\3x^2 - 7x - 5x^2 - 9x > 0\\\\- 2x^2 - 16x > 0\qquad/:(-2)\\\\x^2+8x<0\\\\x(x+8) < 0\\\\x_1=0\qquad\qquad x_2+8=0\\x_1=0\qquad\qquad x_2=-8\qquad\qquad\ a=1>0\\\\x\in\big({-}8,\, 0\big)[/tex]

Zobacz obrazek Unicorn05